Legislation Authority Overlap: Parliament versus Constitutional Court in Indonesia - Ahmad Mustarudin Efendi (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
AbstractThe Indonesian House of Representatives has an authority to form laws together with the President, which may limit the authority of the Constitutional Court. On the other hand, the Constitutional Court has an authority to examine the suitability of the law against the 1945 Constitution. These facts have triggered a dispute between the Parliament and the Constitutional Court. The topic of this article consists of two main points. The first, what is the task form and the authority of the Parliament and the Constitutional Court? The second, what is the ultra petita authority of the Constitutional Court that causes the redundancy of legislative authority between the Parliament and the Constitutional Court? The research results reveal that in the view of the trias politica theory, based on the principle of checks and balances, the legislation authority is entirely in the hands of legislative and executive. In addition, the basis of the overlapping of the authority between the House of Representatives and the Constitutional Court is related to the ultra petita of the Constitutional Court’s decisions, which often makes new norms as a substitute for the norms that are canceled.AbstrakAdanya kewenangan Dewan Perwakilan Rakyat (DPR) membentuk norma undang-undang bersama dengan Presiden yang dapat membatasi kewenangan Mahkamah Konstitusi (MK) dan adanya kewenangan MK untuk menguji undang-undang terhadap Undang-Undang Dasar (UUD) menimbulkan sengketa antara DPR dan MK.  Topik kajian dalam penulisan artikel ini terdiri dari, pertama bagaimana bentuk tugas dan kewenangan lembaga DPR dan MK? Dan kedua bagaimanakah kewenangan ultra petita MK yang menjadi penyebab timbulnya overlapping kewenangan legislasi lembaga DPR dan MK? Dari hasil penelitian ditemukan bahwa pandangan teori trias politica yang mendasarkan pada prinsip checks and balances menempatkan kewenangan legislasi berada sepenuhnya pada tangan legislatif dan eksekutif, selain itu yang menjadi dasar dari timbulnya overlap kewenangan DPR dan MK adalah kaitannya dengan ultra petita dalam putusan MK yang seringkali membuat norma baru sebagai pengganti dari norma yang sudah dibatalkan.DOI: https://doi.org/10.22304/pjih.v5n1.a3